2023
DOI: 10.1002/cbic.202300033
|View full text |Cite
|
Sign up to set email alerts
|

Polypyridyl CoII‐Curcumin Complexes as Photoactivated Anticancer and Antibacterial Agents

Abstract: Four new Co II complexes, [Co(bpy) 2 (acac)]Cl (1), [Co-(phen) 2 (acac)]Cl (2), [Co(bpy) 2 (cur)]Cl (3), [Co(phen) 2 (cur)]Cl (4), where bpy = 2,2'-bipyridine (1 and 3), phen = 1,10-phenanthroline (2 and 4), acac = acetylacetonate (1 and 2), cur = curcumin monoanion (3 and 4) have been designed, synthesized and fully characterized. The X-ray crystal structures of 1 and 2 indicated that the CoN 4 O 2 core has a distorted octahedral geometry. The photoactivity of these complexes was tuned by varying the π conj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(33 citation statements)
references
References 64 publications
0
33
0
Order By: Relevance
“…47,49 Curcumin complexes (2, 3) showed a sharp IR band near 1515 cm −1 corresponding to the α,β-unsaturated ketone's C�C bonds. 47,49 The HRMS of complexes 1−3 in MeOH showed a molecular ion peak corresponding to the [M − Cl] + species (Figures S13−S15). Complexes 2 and 3 showed a strong absorption band near 430 nm in 10% aq.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…47,49 Curcumin complexes (2, 3) showed a sharp IR band near 1515 cm −1 corresponding to the α,β-unsaturated ketone's C�C bonds. 47,49 The HRMS of complexes 1−3 in MeOH showed a molecular ion peak corresponding to the [M − Cl] + species (Figures S13−S15). Complexes 2 and 3 showed a strong absorption band near 430 nm in 10% aq.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…79 As the anticancer activities of 2 and 3 were found to improve remarkably on light exposure, these complexes would probably induce apoptotic cell death by ROS generation as is reported for numerous curcumin-metal complexes. [47][48][49]61 The basic concept of PDT also relies on photosensitizer-induced ROS generation at the target cancer site because the photosensitizers have the ability to generate singlet oxygen ( 1 O 2 ) via a type-II energy transfer pathway upon light excitation. 16 Our computational study revealed that singlet−triplet splitting of complexes 2 and 3 is sufficient to produce 1 O 2 (Figure 2(e)).…”
Section: Solubility and Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…T he coordination chemistry of oxyanions as ligands in "classical" coordination complexes has been extensively studied, and a large number of transition metal complexes containing ligands such as CO 3 3−14 However, several features of the reported synthesis and characterization led us to question the identity of the isolated complex. First, the reaction was carried out under aerobic conditions; air oxidation of solutions of Co(II) in the presence of amine ligands is often facile, and while Co(II) complexes containing two bipy ligands have been isolated under aerobic conditions, 15,16 oxidation to Co(III) cannot be excluded. A Co(III) oxidation state was further supported by examination of the reported X-ray structure; the Co−N bond lengths, which range from 1.913 to 1.944 Å, are consistent with those found in Co(III) complexes containing two bipy ligands 17,18 and are significantly shorter than those in analogous Co(II) complexes (d Co−N ∼ 2.1 Å).…”
mentioning
confidence: 99%
“…Therefore, the recent report by Pan and co-workers of only the second structurally characterized example of chelated hydrogenborate in the Co­(II) complex [Co­(bipy) 2 O 2 BOH]·[B 5 O 6 (OH) 4 ]·H 3 BO 3 ·H 3 O·H 2 O (bipy = 2,2′-bipyridine) was of interest, given our extensive work on the coordination chemistry of oxyanions. However, several features of the reported synthesis and characterization led us to question the identity of the isolated complex. First, the reaction was carried out under aerobic conditions; air oxidation of solutions of Co­(II) in the presence of amine ligands is often facile, and while Co­(II) complexes containing two bipy ligands have been isolated under aerobic conditions, , oxidation to Co­(III) cannot be excluded. A Co­(III) oxidation state was further supported by examination of the reported X-ray structure; the Co–N bond lengths, which range from 1.913 to 1.944 Å, are consistent with those found in Co­(III) complexes containing two bipy ligands , and are significantly shorter than those in analogous Co­(II) complexes ( d Co–N ∼ 2.1 Å). , Similarly, the reported B–O bond lengths are almost exactly the same as the C–O distances found in Co­(III) amine complexes containing chelated carbonate. ,, Finally, we were concerned about the presence of an H 3 O + ion in the structure.…”
mentioning
confidence: 99%